High- and moderate-intensity training modify LPS-induced ex-vivo interleukin-10 production in obese men in response to an acute exercise bout - Gerosa-Neto, José [UNESP]; Monteiro, Paula Alves [UNESP]; Inoue, Daniela Sayuri [UNESP]; Antunes, Barbara Moura [UNESP]; Batatinha, Helena; Dorneles, Gilson Pires; Peres, Alessandra; Rosa-Neto, José Cesar; Lira, Fabio Santos [UNESP] (Elsevier, 2020)
The aim of this study was to evaluate the inflammatory (peripheral and lipopolysaccharide (LPS)-stimulated released from whole blood) and metabolic (glucose and insulin) profile of inactive obese men in response to two isoenergetic models of aerobic exercise training (~300 kcal each exercise session). Twenty-two participants (28.7 ± 1.6 years; BMI = 34.4 ± 0.1 kg/m2) were randomized into two groups: I) HIIT: high-intensity interval training (10× 1 bout: 1 min − 100% Maximal Aerobic Velocity) or II) MICT: moderate-intensity continuous training (65% Maximal Aerobic Velocity; kcal equal to HIIT). Both groups trained three times per week for 6-weeks. Fasting blood samples were collected before and 0, 30, and 60 min after exercise during the first and last training sessions for evaluation of: I) MIP-1ɑ, insulin, glucose, visceral and subcutaneous fat depots, oral glucose tolerance test, and homeostatic model assessment of insulin resistance (HOMA-IR) index; II) Peripheral (TNF-α, IL-6, and IL-10) and LPS-stimulated release of TNF-α and IL-10 were analyzed before, 0, and 60 min after sessions. IL-6 concentration remained elevated up to 60-min after the acute exercise session (p < 0.001), and IL-10 concentration was higher after 30 and 60-min (p = 0.001) compared to rest, independent of training period and protocol. AUC of IL-10 presented effect of type of training (p = 0.023) with MICT group showed significantly higher values than the HIIT. The ex-vivo assay showed higher IL-10 secretion in response to LPS immediately (p = 0.003) after both acute MICT and HIIT exercise sessions, independent of training period. Fifteen subjects presented decreased HOMA-IR after 6-weeks and seven presented an increase in this index. When we excluded the two least responsive subjects, it was possible to observe a decrease in HOMA-IR (p = 0.020) after training. Taken together, our results suggest that both HIIT and MICT (with same energy expenditure) promote similar effects on HOMA-IR and led to elevations in IL-10 production in LPS-stimulated whole blood, suggesting that leukocytes had an enhanced ability to secrete anti-inflammatory cytokines after the exercise bout.
Keywords: Aerobic training; Anti-inflammatory; Isoenergetic training; Short-term training